Tarnania fenestralis (Meigen, 1818) (Díptera: Micetophilidae) associated with the fungus Pleurotus eryngii (DC.) Quél. - Tobar, Veronica; Notario, Antonio; Castresana, Luis Miguel (Forest Systems, 2010)
Extensive natural mushroom cultivations of Pleurotus eryngii (DC.) Quél. were studied in their main productive area, the northwest of Segovia province, Spain, identifying a new parasite for this fungus, Tarnania fenestralis (Meigen, 1818) (Diptera: Micetophilidae). The prevalence of parasitization reaches 20.4% of the yield, the main damage being in the destruction of internal tissues of the carpophores, resulting in crop depreciation. Due to the high incidence of parasitization by the dipteran in the mushroom, as well as its abundance, the nematocerous fungivore T. fenestralis may be considered the main and most important parasite of extensive P. eryngii productions of all the zone in which the investigation is made.